Ensaios sobre câmbio e competitividade - Siessere, Arthur Tornatore (2018)
This work is composed of three essays dealing with the themes of exchange rate and competitiveness for the Brazilian, North American and European economy. The first part aims to verify empirically the validity of the theory of purchasing power parity and the Balassa-Samuelson effect for the Brazilian and North American economy, from 1948 to 2016. The second part seeks to analyze the relationship between exchange rate and wages for the brazilian economy in the post-trade liberalization period, from 1999 and 2015. The third part analyzes the influence of intellectual capital and its components on the national wealth of European Union countries. Thus, theories about the topics are presented an, econometric techniques of time series and analysis panel data has been used to analyze the data collected. The results of the first essay showed that there is no causal relationship between PPP and the Balassa-Samuelson effect, in addition the tests revealed a long-term causality between the variables. The results of the second part did not show evidence of cointegration between the exchange rate and wages, suggesting that, in the period analyzed, it is not possible to conclude that there is any relationship between the exchange rate and wages for the Brazilian economy. However, Granger's causality tests suggest that over time wages cause changes in the exchange rate. The results of the third research fail to find evidence of the influence of structural capital on national wealth, on the other hand, relational capital was positive and significant in all estimated models. Finally, despite finding evidence of a positive moderating effect between innovation and sophistication in the relationship between human capital and national wealth, it is not possible to validate that there is a moderating effect on the relationship between intellectual capital and national wealth.